„Aevum quod est angeli duratio”. Wiekuistość, czyli między wiecznością a czasem - KOWALEWSKA, Małgorzata (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
Exploring the essence of aevum and its relation to eternity and time is among the most interesting issues undertaken by philosophers already in the ancient times. Even an introductory analysis of the literature on the subject demonstrates that the object of research in question, as well as the philosophical approaches to it, has a liminal character. Aevum is seen as being between time and eternity, with its delineation rather unclear and its essence difficult to grasp. It appears to be the mode of existence of certain beings which remain between the visible and subject to movement and time on the one hand, and the transcendental in the highest degree on the other. Thus the beings in question exhibit an intermediary nature: in the chain of being, they are situated between what they transcend and what transcends them. The development of the conceptions of aevum and beings to which aevum belongs was triggered by astronomical theories in which spiritual substances were considered as responsible for the movement of stars and cosmic spheres, as well as by metaphysical speculations on the degrees of being, which had their roots in the Neoplatonic ideas of emanation, and by Biblical teaching on angels and demons. The current aricle is focused on the two former sources of the philosophical concept of aevum. Translated by Dorota Chabrajska